Bahasa Indonesia: english - Syahdia, Elfitri; Syahrawati, My (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2020)
Misuse and overuse of insecticides by farmers in controlling the brown planthopper or BPH (Nilaparvata lugens), such as over-spraying, over-doses, and mixing more than two insecticides in one application, caused many environmental problems, including resistance. This study aimed to measure the resistance rate of BPH from Payakumbuh Sub-district, West Sumatera Province against BPMC (buthylphenylmethyl carbamate) insecticide. This study used a complete randomized design that consisted of 5 treatments and 5 replications. The treatment was carried out at different concentrations: 0.5 recommended concentration (0.5 ml/l), 1 recommended concentration (1 ml/l), 1.5 recommended concentration (1.5 ml/l), 2 recommended concentration (2 ml/l) and control (without insecticide). The results showed that the higher dose of insecticide, the higher mortality of BPH nymphs. The number of nymphs that succeed to becoming adult decreased when the dosage of insecticide used was increasing. Based on the resistance ratio, the BPH from Payakumbuh is still susceptible to BPMC insecticide. The LC 50 and LC 95 were 0.97 and 2.09 ml on the first day after the application. Keywords: Brown planthopper, resistance, BPMC, mortality, lethal concentration